Digital-based SME Innovation Development Strategy: Marketing, Entrepreneurship Insight and Knowledge Management - Merdika Mansur, Daduk (Golden Ratio of Mapping Idea and Literature Format, 2022)
The success factor for the knowledge sharing from a management point of view, RBV views that substantially the success factor for knowledge sharing is fully held by business leaders. Leaders are seen as the main driving force for business organizations, because all policies and work procedures that a leader will implement in the organization will shape perceptions, culture and will also affect future organizational activities. Support from all parties is needed, not only the role of the leader but also the cooperation and involvement of employees. Refer to the resume of 20 recent Scopus indexed publications. Mapping the literature in this study provides several clues and propositions which can be clearly seen in this paper.